A survey of resource allocation in non-orthogonalmultiple access systems - Zhengqiang WANG; Qu CHENG; Zifu FAN; Xiaoyu WAN (Dianxin kexue)
Non-orthogonalmultiple access(NOMA)is an important candidate technology of the fifth generation(5G)wireless network,which canmeet the low latency,low power consumption,high reliability,high throughput,wide coverage requirements of the next generationmobile communication systems.NOMA utilizes superposition coding at the transmitter and successive interference cancellation at the receiveRto allow several users’datamultiplexing in the same resource block.It improves the spectrum efficiency compared with the traditional orthogonalmultiple access.The research status of resource allocation of NOMA systems was summarized including single-carrier NOMA resource allocation,multi-carrier NOMA resource allocation,cooperative NOMA relay resource allocation,and cooperative NOMA resource allocation under hardware impairment conditions.Finally,themain problems in the current study were summarized and the research challenges and some future research directions of NOMA resource allocation technology were discussed.